DEVELOPMENT OF INTERACTIVE LEARNING MEDIA “RUMAH RANIA” TO IMPROVE STUDENTS’ CULTURAL AND CITIZENSHIP LITERACY SKILLS IN ELEMENTARY SCHOOL - Agus Mulyono; Sutji Muljani; Tri Mulyono (Universitas Majalengka, 2026)
The low of cultural and citizenship literacy skills in elementary school level remain a significant challenge that urgently requires innovative solutions, particularly through the use of instructional media that adaptive to technological advancements. This study aims to: (1) analyze the needs of teachers and students to interactive learning media, (2) design the prototype of the learning media, (3) assess the validity and practicality of the media, and (4) to assess the suitability and practicality of using interactive learning media Rumah Rania to improve cultural and citizenship literacy skills of elementary school students. This study employed a Research and Development (R&D) approach using the ADDIE development model. Data was collected through observation, user feedback questionnaires, expert validation, usability, practicality, and effectiveness testing. The results of the study show that: (1) A needs analysis has shown that teachers require interactive learning media that are easy to use and relevant to the curriculum, while the students prefer visual-based learning, videos, quizzes and engaging, easy-to-understand educational games; (2) The development of the media was carried out using the ADDIE model, focusing on analysis, design, development and implementation; (3) The validation results show that the media has a very high level of suitability, with a score of 91,0% from media experts and 88.0% from subject matter experts. The high Aiken’s V index scores in both validation studies—0.875 for the media validation and 0.887 for the content validation—indicate that all the indicators developed are relevant, appropriate and capable of significantly supporting the learning achievement. Meanwhile, from a practical perspective, the validation results from the observer showed a Percentage of Agreement (PoA) of 97,9%, which falls within the ‘Highly Reliable’ category. The results of the effectiveness test carried out on 28 year 6 students at Eelemntary School 01 Jatirokeh showed an average N-Gain score of 0.729. The data distribution indicated that 75.9% of students showed a moderate improvement, whilst 24.1% showed a high level of improvement. Based on these findings, the Rumah Rania interactive learning media has been found to be valid, practical and worthy of recommendation as an alternative learning media that supports the improvement of students cultural and citizenship literacy skills and learning quality in elementary schools.